Economic Empowerment of Underdeveloped Village Women Based on Islamic Philanthropy (Study on Members of the Women-Based Microfinance Cooperative (KKM-BP) Assisted by LAZ HARFA, Pandeglang Regency) - Najmudin Najmudin; Isti Nuzulul Atiah; Elif Pardiansyah (Jurnal Studi Gender dan Anak, 2022)
This study aims to describe the economic empowerment of disadvantaged rural women based on Islamic Philanthropy. The research method used in this research is descriptive qualitative research. The location of this research is in Kertaraharja Village, Pandeglang Regency. The population in this study were all women who were managers and members of the Women-Based Microfinance Cooperative (KKM-BP). The sample used is purposive sampling. Data collection techniques are to be carried out in the form of interviews, observation, and documentation. The analytical tool used to analyze the qualitative data in this study is QDA Miner Lite with the Miles and Huberman Model data analysis technique, which divides data analysis into three stages, namely data reduction, data supply, and conclusion drawing. The results of this study indicate that the economic empowerment of disadvantaged rural women by the Amil Zakat Harapan Dhuafa Institution (LAZ Harfa) is carried out by forming a Women-Based Microfinance Cooperative (KKM-BP), the initial capital given to KKM-BP is a grant sourced from philanthropic funds, the management of KKM-BP is carried out independently by members who are accompanied by village assistants assigned by LAZ Harfa. The establishment of the KKM-BP in the village of Kertaraharja led the women of disadvantaged villages to reach productive sources that could increase their income, fulfill their basic needs so that they were free from hunger, ignorance, and pain, and were involved in making important decisions in the development of the KKM-BP. it fits Suharto's indicators of empowerment, namely (a) fulfilling basic needs, (b) reaching productive sources that allow them to increase their income and obtain the goods and services they need, and (c) participating in development processes and decisions. -decisions that affect them.